Co-encapsulation of coenzyme Q10 and vitamin E: A study of microcapsule formation and its relation to structure and functionalities using single droplet drying and micro-fluidic-jet spray drying. (April 2019) - Huang, Elaine; Quek, Siew Young; Fu, Nan; Wu, Winston Duo; Chen, Xiao Dong
Abstract: The objective of this research was to study the co-encapsulation of Coenzyme Q10 (CoQ10 ) and vitamin E (VE) using single droplet drying (SDD) and micro-fluidic-jet spray drying (MFJSD), to study the particle formation-structure-function relationships of the microcapsules. Single droplets of selected CoQ10 and VE-containing emulsions were studied for their particle formation under convective drying (at 70 and 90 °C for 10 min) and rehydration processes using the SDD device. The emulsions were also spray-dried (at 160 and 190 °C) by MFJSD to form monodisperse microcapsules, followed by analyses of powder properties and functionalities. Results from SDD showed emulsion droplets with 30% w/w solids content were associated with earlier crust formation (30 s faster) and less particle shrinkage during drying compared to those with 10% w/w solid content. Comparing the spray-dried microcapsules produced from the emulsions containing 30% and 10% w/w solids content, the former gave larger particle size (172–175 μ m vs. 116 μ m ), higher microencapsulation efficiency (ME) (98–99% vs. 96%), lower tapped density (0.532–0.599 g/cm 3 vs. 0.406–0.502 g/cm 3 ) and better flow properties (Carr's index of 22.06–29.19% vs. 22.70–40.64%). Overall, the CoQ10 and VE retention, antioxidant capacities and colour of the microcapsules were relatively stable when spray-dried at 190 °C than at 160 °C. Highlights: Coenzyme Q10 and vitamin E were co-encapsulated in powder microcapsules. Formation-structure-function relationships of microcapsules were investigated. Emulsions with higher solids content formed skin earlier during drying. Emulsions with higher solids content produced better quality microcapsules. Higher spray drying temperature produced more stable microcapsules.